Poly(propylene)/waste vulcanized ethylene- propylene-diene monomer (PP/WEPDM) blends prepared by high-shear thermo-kinetic mixer. (October 2018) - Simsek, Eren; Oguz, Oguzhan; Bilge, Kaan; Citak, Mehmet Kerem; Colak, Oguzhan; Menceloglu, Yusuf Z
Polypropylene (PP)–waste elastomer blends are particularly attractive as an economical way of producing sustainable materials, relieving the stress on the environment. Although PP is a commodity thermoplastic finding employment in various applications, its relatively low impact strength might be a significant factor limiting the variety of uses in many industries. Extensive consumption of thermoset elastomers has been a worldwide waste disposal problem. Here, we describe a facile, economical method for reuse of waste ethylene-propylene-diene monomer (EPDM) rubber to produce impact resistant blend materials with the PP via a high-shear thermokinetic mixer. In these blends, waste EPDM was used in various concentrations ranging from 20 to 80 wt%, as the remaining part, PP acts as a carrier matrix or a physical binder depending on the concentration in the blend. Briefly, fivefold increase was achieved in the impact resistance of PP by the addition of 60 wt% EPDM waste. The blend with 80 wt% waste EPDM shows characteristics similar to a thermoplastic elastomer. The conclusion of the study is that the blending method is quite effective to produce high-performance blend materials consisting of high concentrations of thermoset waste which addresses the worldwide disposal problem of waste thermoset rubbers.